2007
DOI: 10.1295/polymj.pj2007036
|View full text |Cite
|
Sign up to set email alerts
|

A Supramolecular Chiroptical Switch Based on Chitosan and Anionic Porphyrin Complex Film

Abstract: ABSTRACT:A supramolecular chiroptical switch based on chitosan and tetrakis (4-sulfonatophenyl) porphine (TPPS) complex films was prepared. The reversible changes of the chirality of the complex films were studied by UV-vis and circular dichroism (CD) spectra. It was found that the chirality of the complex films can be wiped off by being exposed to NH 3 gas and subsequently recovered by being exposed to moist HCl gas. The complex film is stable and can stand at least 20 cycles of the switching to NH 3 and HCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…459 Very significant is the case of achiral 5,10,15,20tetrakis(4-N-methylpyridyl)porphine (TMPyP, 48, Figure 33), which generates induced ECD signals around 450 nm upon intercalation into DNA thin films; 460 in particular, the DNA/ 48 complex system was intensively studied as pH-sensitive reversible chiroptical switch by alternate exposure to HCl and NH 3 vapors. 461,462 Remarkable ECD signals were also found in thin films of several achiral porphyrins covalently or notcovalently incorporated to other biopolymers, including poly(L-glutamic acid), 463 chitosan, 464 and chitosan−methylcellulose. 465 As described above, the air/water interface is a 2D-confined space where the spontaneous breaking of symmetry of achiral molecules may happen through intermolecular interfacial interactions.…”
Section: Ecd In Thin Films Of Large π-Conjugated Molecular Systemsmentioning
confidence: 96%
“…459 Very significant is the case of achiral 5,10,15,20tetrakis(4-N-methylpyridyl)porphine (TMPyP, 48, Figure 33), which generates induced ECD signals around 450 nm upon intercalation into DNA thin films; 460 in particular, the DNA/ 48 complex system was intensively studied as pH-sensitive reversible chiroptical switch by alternate exposure to HCl and NH 3 vapors. 461,462 Remarkable ECD signals were also found in thin films of several achiral porphyrins covalently or notcovalently incorporated to other biopolymers, including poly(L-glutamic acid), 463 chitosan, 464 and chitosan−methylcellulose. 465 As described above, the air/water interface is a 2D-confined space where the spontaneous breaking of symmetry of achiral molecules may happen through intermolecular interfacial interactions.…”
Section: Ecd In Thin Films Of Large π-Conjugated Molecular Systemsmentioning
confidence: 96%
“…It can form stable J-aggregate or H-aggregate, which depends on the pH value and ionic strength in the system. TPPS aggregates can be easily induced to show chirality by many cationic chiral and achiral templates, such as L-(or D-) Trp film, 24 gemini-Type Amphiphiles, 25 polylutamic acid 26 and polylysine, 27 chitosan, 28 etc. Usually, these templates are just cationic, which can be directly interacted with the anionic TPPS.…”
mentioning
confidence: 99%
“…[48][49][50][51][52][53] Various artificial photo-devices based on the chiral porphyrin supermolecules are anticipated to be potentially useful for the practical applications. [54][55][56][57] In our previously reported work, we found that the random symmetry breaking in the synthesis of a chiral octahedral cobalt complex (cis-[CoBr(NH 3 )(en) 2 ]Br 2 ) could be transferred in the supramolecular self-assembly process of anionic porphyrin derivatives. 58 What we are interested in is how did the chirality at the small molecular level transfer to the advanced supramolecular level.…”
Section: Introductionmentioning
confidence: 99%